2003
DOI: 10.1073/pnas.1834545100
|View full text |Cite
|
Sign up to set email alerts
|

The p7 polypeptide of hepatitis C virus is critical for infectivity and contains functionally important genotype-specific sequences

Abstract: The role of the hepatitis C virus (HCV) p7 protein in the virus life cycle is not known. Previous in vitro data indicated that this 63-aa polypeptide is located in the endoplasmic reticulum and has two transmembrane domains (TMDs) connected by a cytoplasmic loop; the aminoand carboxyl-terminal tails are oriented toward the endoplasmic reticulum lumen. Furthermore, recent in vitro studies suggested that HCV p7 could function as a virus-encoded ion channel. It might therefore be a relevant target for future drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
188
2
8

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(206 citation statements)
references
References 31 publications
(38 reference statements)
6
188
2
8
Order By: Relevance
“…In a reverse genetics study of bovine viral diarrhea virus, it was shown that a large in-frame deletion of p7 does not affect RNA replication but prevents the formation of infectious virions (15). The role of HCV p7 in the virus life cycle is unclear at present, but a genome-length HCV RNA in which the p7 sequence had been deleted was not infectious upon intrahepatic inoculation in a chimpanzee (56). A subsequent analysis of genome-length molecular clones of HCV containing chimeric intertypic p7 sequences revealed that there was a genotype-specific p7 requirement localized to the N-and/or C-terminal regions of this polypeptide, suggesting that it may interact with other proteins encoded by HCV in a genotype-specific manner (56).…”
Section: Discussionmentioning
confidence: 99%
“…In a reverse genetics study of bovine viral diarrhea virus, it was shown that a large in-frame deletion of p7 does not affect RNA replication but prevents the formation of infectious virions (15). The role of HCV p7 in the virus life cycle is unclear at present, but a genome-length HCV RNA in which the p7 sequence had been deleted was not infectious upon intrahepatic inoculation in a chimpanzee (56). A subsequent analysis of genome-length molecular clones of HCV containing chimeric intertypic p7 sequences revealed that there was a genotype-specific p7 requirement localized to the N-and/or C-terminal regions of this polypeptide, suggesting that it may interact with other proteins encoded by HCV in a genotype-specific manner (56).…”
Section: Discussionmentioning
confidence: 99%
“…p7 channels displayed both single-channel and burst-like behaviour, consistent with channel-pore dualism. Interest in p7 as a potential ion channel therapeutic target was stimulated by chimpanzee studies that showed it to be essential for HCV propagation in vivo (Sakai et al, 2003).…”
Section: Hcv P7mentioning
confidence: 99%
“…As this overlaps with the IRES, there is considerable interest in understanding how this region might modulate translation and replication, which are unlikely to occur simultaneously on the same RNA template. The 3፱ NCR has been found to contain a nonessential variable region, a poly-U/UC tract that must be more than 26 nucleotides long, followed by a highly conserved and essential 3፱X domain 55,57,76 . Recently a conserved stem-loop structure within the NS5B coding region, 5BSL3.2, was found to be required for RNA replication 78 .…”
Section: Mechanisms Of Hcv Rna Replicationmentioning
confidence: 99%
“…Further studies indicated that 5BSL3.2 forms functionally important long-distance base pairs bled and shown to be infectious by direct intrahepatic injection of RNA transcripts into chimpanzees 52,53 . These infectious clones were used to show that all viral enzyme activities, the p7 gene and the correct genomic 3፱ end are necessary for HCV replication in vivo [54][55][56] . In contrast, the hypervariable N-terminal region of E2 is dispensible 57 .…”
Section: Mechanisms Of Hcv Rna Replicationmentioning
confidence: 99%